Análisis del impacto socioeconómico de los Microcréditos otorgados por la Cooperativa de Ahorro y Crédito San Sebastián - Loja, Períodos 2007-2010 - Carrión Cocios, Verónica Alexandra (2017)
In Ecuador there are a variety of financial institutions engaged in financial intermediation that offer the same products and services of various kinds becoming an economic support system and to promoting economic and social development of the country in Ecuador . Within financial activities is the business microcredit, a loan whose principal recipient families with limited financial resources in order to support them to engage in small businesses with the aim of achieving a higher level of income, improving their living standards. El presente trabajo de investigación tiene como objetivo general: Analizar el impacto generado por los microcréditos otorgados a los socios de la Cooperativa de Ahorro y Crédito San Sebastián-Loja en el período 2007-2010, pretendiendo de esta manera aportar a la entidad con información verídica De cómo se han beneficiado los socios desde el punto de vista social y económico a través del financiamiento, y de esta manera continúan la institución con su gestión de dinero captar y colocar en los sectores más vulnerables de la ciudad de Loja. In the fulfillment of the first specific objective, information was collected through the observation and the application of surveys, techniques that allowed to know real and exact data on the economic and social situation of the members of the Cooperative. Based on the information obtained, social, economic and institutional indicators were used to establish the positive and negative socioeconomic effects of microcredit granted to members by the Institution. Subsequently to know how microcredits have affected the living conditions of the partners, for which the results obtained based on social and economic indicators were analyzed and interpreted. In addition, we used the deductive, inductive, analytical, synthetic and techniques such as the bibliographic collection and the survey that served to meet the objectives and facilitate the analysis of the data obtained. Finally, it is concluded that the San Sebastián Savings and Credit Cooperative has had a positive impact on the socio-economic development of its partners, focusing mainly on women, who have been able to become independent and provide financially in their home, through this program the partners Have been able to perform in different economic activities allowing them to maintain stable income, which helps them to cover their needs and thus improve their living conditions.